A study of the covid-19 infographic design issued by Indonesian Ministries in online media - Ryan Sheehan Nababan; Peter Ardhianto (International Journal of Visual and Performing Arts, 2022)
The Indonesian Government Ministry has carried out a health campaign to prevent the spread of COVID-19. One of his campaign strategies is to publish infographics in online media. This study describes the existence of infographics produced by the Ministry of Government of the Republic of Indonesia during the COVID-19 pandemic. This research design is qualitative descriptive research with a case study approach. Data were obtained by random sampling through digital data browsing on the internet, recording, in-depth observation, and content analysis. The data obtained were analyzed using interactive analysis. The results of this study reveal that the infographics produced by the Ministry of the Government of Indonesia consist of various types and forms. Each type and form has a constituent structure, Vitruvius principles, and aspects, which are almost the same pattern. Furthermore, the research team found that the infographic aims to convey persuasive appeals, news, statistical data, and messages regarding preventing the spread of COVID-19. The various infographics also play a role in increasing public awareness about the dangers of COVID-19, being disciplined in implementing health protocols and playing a role in suppressing the spike in the spread of COVID-19 in all regions in Indonesia